Publisher Rights for Quality Journalism: Opportunities and Challenges in Indonesia - Jayus, Jayus; Abdullah, Assyari; Sumaiyah, Sumaiyah; Wilindaya, Infa; Mustafa, Mustafa (Universitas Muhammadiyah Yogyakarta, 2026)
The Evolution of digital technology has transformed the global media, affecting the way news is produced, distributed, and consumed. With digital giants like Google, Facebook, and Instagram dominating the online field, local news publishers have had a tough time getting adequately paid for their content. Presidential Regulation Number 32 of 2024 concerning the Corporate Responsibility of Digital Platforms to Support Quality Journalism. This regulation is commonly referred to as ‘Publisher Rights’. Publisher Rights intends to level that playing field by giving digital platforms equal remuneration to local and national news publishers. This article will analyze the opportunities and challenges of the Publisher Rights regulation in Indonesia, along with experiences in Australia, Canada, France, and Spain. Using a qualitative approach with document analysis method on regulations, Policy Papers, Scientific Journals, books, company reports, and government reports. According to the results presented in this article, the implementation of the regulation offers a significant opportunity to support the sustainability of quality journalism in Indonesia, as evidenced by the compensation paid by digital platforms to local and national media. However, several obstacles to the implementation of Publisher Rights in Indonesia that have emerged are resistance from digital platforms, difficulties in negotiating with small publishers, and transparency regarding compensation. To ensure the soundness and effectiveness of Publisher Rights in Indonesia, the government, news publishers, and digital platforms must work closely together. Consequently, this may help illuminate how these regulatory frameworks might enhance the media ecosystem and bolster quality journalism in the current digital era.